Some inequalities for two simplices in the Euclidean space En - Juanjuan Pan; Xuewu Zuo (Heliyon, 2023)
Simplices are used as building blocks to construct an interesting class of topological spaces called simplicial complexes, which exhibit remarkable symmetric properties. In this paper, we study the problems of inequalities for two simplices in the Euclidean space En. We establish some new inequalities for the vertex distances of two simplices and obtain some generalizations of the classical Neuberg-Pedoe inequality.